Europe After COVID-19: A New Role for German Leadership? - Francesco Saraceno (Intereconomics, 2021)
The German change of attitude concerning fiscal policy and the mutualisation of efforts to fight the pandemic is driven by self-interest, and as such might be structural.
Keywords: 330; Coronavirus; EU-Politik; Finanzpolitik; EU-Staaten